The crystal structure of Ni-rich gordaite–thérèsemagnanite from Cap Garonne, France. (14th March 2019) - Mills, Stuart J.; Missen, Owen P.; Favreau, Georges
Abstract: The crystal structure of Ni-rich gordaite–thérèsemagnanite has been determined from a sample collected at pillar 80 in the North mine, Cap Garonne, Var, France. The structure was refined to R 1 = 0.0693 for 935 reflections with I > 2σ( I ). The mineral is isostructural with gordaite, forming a layered structure with an extensive hydrogen-bonding network. The possible polytypic relationship between gordaite, thérèsemagnanite and guarinoite is also discussed. The guarinoite formula (Zn, Co, Ni)6 (SO4 )(OH, Cl)10 ·5H2 O is also likely to be incorrect and is more likely to be Na(Zn, Co)4 (SO4 )(OH)6 Cl·5–6H2 O, meaning that guarinoite is equivalent to Co-rich gordaite-2 H and would not be a distinct mineral species.